A triple-functionalised metal centre-catalyzed enantioselective multicomponent reaction. Issue 19 (29th August 2018) - Wei, Qinghua; Ma, Xiaochu; Chen, Jianghui; Niu, Li; Yang, Xi; Xia, Fei; Liu, Shunying
Abstract : A model of a triple-functionalised metal centre for the discovery of unprecedented enantioselective reactions was exquisitely developed by using a Rh I /(DHQ)2 PHAL catalyst system via multiple coordination interactions with different ligands and substrates. Abstract : An enantioselective multi-component reaction (MCR) was exquisitely developed by using a catalytic model of a triple-functionalised metal centre in a Rh I /(DHQ)2 PHAL system via multiple coordination interactions. The catalytic reactivity of the Rh I centres was critically modulated by a complex dissociation process rather than a common ligand exchange process. The developed MCR offers a mild, atom-efficient, and step-economical method to construct 3, 3-disubstituted oxindoles with high diastereo- and enantioselectivities. This study provides an efficient example that gives insight into a strategy for the discovery of MCRs by using high-coordination-number transition metals as multiple functional catalytic centres.